2017
DOI: 10.2514/1.j055844
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Scattering for Rotational and Translational Symmetric Structures in Nonuniform Potential Flow

Abstract: An efficient approach is proposed to predict acoustic scattering with nonuniform potential flow effects for structures with rotational and translational symmetries. The convected wave equation is transformed to Helmholtz and Laplace equations using a time transformation. The boundary-element method is used to formulate scattering by rotationally symmetric structures as two separate block circulant matrix equations and, similarly, as two separate block Toeplitz matrix equations for structures with translational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…25,26 The effect of non-uniform potential flow and flow-induced noise can be taken into account by well-known Taylor transformation. 27,28 Taylor's transformation is a simple time transformation that decouples the mean-flow and acoustic-field calculations and is valid under assumptions of low Mach number. 29 Astley and Bain 64 proposed an approximate formulation for wave propagation in non-uniform mean flow based on Taylor transformation.…”
Section: Bem3d For Aero-acoustic Problemsmentioning
confidence: 99%
“…25,26 The effect of non-uniform potential flow and flow-induced noise can be taken into account by well-known Taylor transformation. 27,28 Taylor's transformation is a simple time transformation that decouples the mean-flow and acoustic-field calculations and is valid under assumptions of low Mach number. 29 Astley and Bain 64 proposed an approximate formulation for wave propagation in non-uniform mean flow based on Taylor transformation.…”
Section: Bem3d For Aero-acoustic Problemsmentioning
confidence: 99%
“…Karimi et al [12] found that applying the BEM to periodic structures leads to the formation of a block Toeplitz matrix due to the translational invariance of the free-space Green's function. The method is termed the periodic boundary element method and has been applied to problems with multi-directional periodicity [13], problems involving rotational symmetry [14] and aeroacoustic predictions of airfoils [15,16]. In the latter case, sequences of linear block Toeplitz systems are considered which are block Toeplitz systems with many right-hand sides.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The LES simulations are able to capture the fluctuating flow noise sources with great detail over a wide range of frequencies. [2][3][4][5][6][7] The LES simulations are able to capture the fluctuating flow noise sources with great detail over a wide range of frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid large eddy simulation (LES)-acoustic analogy techniques have been developed that provide a high-fidelity approach to predict the flow induced noise from a body submerged in the flow. [2][3][4][5][6][7] The LES simulations are able to capture the fluctuating flow noise sources with great detail over a wide range of frequencies. An incompressible large eddy simulation was performed by Wang and Moin 2 to simulate turbulent flow over a flat strut, with the predicted hydrodynamics comparing well with experimental results reported by Blake.…”
Section: Introductionmentioning
confidence: 99%